2001
DOI: 10.1034/j.1399-6576.2001.045004510.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of olprinone, a phosphodiesterase III inhibitor, in an asthmatic patient

Abstract: Phosphodiesterase (PDE) III exists in airway smooth muscles. In addition, PDEIII inhibitors have been suggested to relax airway smooth muscle by increasing intracellular cAMP concentrations. We report a successful use of olprinone, a PDEIII inhibitor, for treatment of an asthmatic attack. A 15-year-old male patient treated with oral theophylline 400 mg x d(-1) was anesthetized with propofol, fentanyl and ketamine for knee joint surgery. Immediately after tracheal intubation, an asthma attack occurred with peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…To determine our hypothesis, after approval of our university ethical committee, we assessed the efficacy of olprinone, a PDEIII inhibitor for treatment of patients showing asthmatic attack under oral theophylline medication, by our direct visualization method using a superfine fiberoptic bronchoscope. Although we had only one case during the research period, we confirmed that olprinone could produce a potent bronchodilation and that this direct visualization method may be more sensitive to determine relaxant effects of olprinone than peak airway pressure [18] (Fig. 5).…”
Section: Application Of the Direct Visualization Methods To Clinical Psupporting
confidence: 78%
“…To determine our hypothesis, after approval of our university ethical committee, we assessed the efficacy of olprinone, a PDEIII inhibitor for treatment of patients showing asthmatic attack under oral theophylline medication, by our direct visualization method using a superfine fiberoptic bronchoscope. Although we had only one case during the research period, we confirmed that olprinone could produce a potent bronchodilation and that this direct visualization method may be more sensitive to determine relaxant effects of olprinone than peak airway pressure [18] (Fig. 5).…”
Section: Application Of the Direct Visualization Methods To Clinical Psupporting
confidence: 78%
“…Olprinone, a specific PDE III inhibitor, has been found to have inotropic and peripheral vasodilatory effects [4], [30]. It is well known that the substrate specificity of PDE III is cAMP > cGMP; therefore, PDE III inhibitors will increase the intracellular cAMP concentration [9][11].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we tested 1 and 10 µg·kg -1 ·min which produce bronchodilatation in humans 7 and in animals 8 were similar or smaller than the doses administered in this study.…”
Section: Responses Of Pial Arterioles To Olprinonementioning
confidence: 99%
“…[10][11][12][13] Recently, it also has been reported that olprinone has a bronchodilator effect, and that bronchial asthma may be treated by iv olprinone in humans 7 and animals, 8 and by inhalation of olprinone in humans.…”
Section: Responses Of Pial Arterioles To Olprinonementioning
confidence: 99%
See 1 more Smart Citation